Utilization of Wheat (Triticum aestivum) and Berseem (Trifolium alexandrinum) Dry Biomass for Heavy Metals Biosorption: Heavy metal sorption by wheat and berseem plant biomass - Iram, Shazia; Ahmad, Khuram Shahzad; Noureen, Sadaf; Jaffri , Shaan Bibi (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2018)
Sorption capacity of wheat (Triticum aestivum) and berseem (Trifolium alexandrinum) biomass was checked against heavy metals i.e. copper (Cu), cadmium (Cd), lead (Pb) and chromium (Cr). Dry biomass was introduced in Erlenmeyer flasks of 250 ml volume to study the effect of varying initial metal concentration, pH and contact time. The filtrates were analyzed using flame atomic absorption spectrophotometer. The adsorption data of wheat and berseem biomass was fitted to Langmuir and Freundlich models. Results exhibited the maximum initial metal concentration (200 mg/L), pH 5 and 9, contact time 60 and 120 min are suitable for biosorption using wheat and berseem plants biomass. It can be recommended from the present study that berseem and wheat biomass can be used for waste water treatment in a cost effective and easy mode.